Increased VO2 peak after a structured exercise-training program is associated with reduced levels of cardiac myosin binding protein C in patients with symptomatic chronic heart failure. (14th October 2021) - Riveland, E.A; Valborgland, T; Ushakova, A; Karlsen, T; Delagardelle, C; Van Cranenbroeck, E.M; Linke, A; Prescott, E; Halle, M; Stoylen, A; Dalen, H; Omland, T; et al.
Abstract: Background: Cardiac myosin-binding protein C (cMyC), a cardiac contractile protein, is a novel biomarker of myocardial injury, rising earlier and disappearing faster than cardiac troponins. It is a promising biomarker for use in triage of patients with chest pain presenting in the emergency department. It also has prognostic significance in patients with heart failure. However, the effects of systematic exercise training on plasma levels of cMyC has previously not been evaluated. Purpose: The aim of this study was to assess the effect of a 12-week exercise training program on changes in plasma levels of cMyC in patients with chronic symptomatic heart failure with reduced ejection fraction (HFrEF). The changes in plasma levels of cMyC in an intervention group, performing structured exercise programs, were compared to those in a control group, instructed to perform regular recommended exercise (RRE) according to current guidelines. Methods: This was a post hoc analysis of the SMARTEX-HF trial in 215 patients with symptomatic HF with Left Ventricular Ejection Fraction (LVEF) <35% and NYHA II-III. The patients were randomly assigned to High Intensity Interval Training (HIIT, n=77), Moderate Continuous Training (MCT, n=65) or RRE, (n=73) for 12 weeks. HIIT and MCT groups constituted the intervention group (IG). Measurements and clinical data were acquired before and after the 12-week intervention. Statistical analysis We divided the patients in two groups with Δ VO2Peak above and below the median of the sample. The absolute changes of cMyC were then compared between the two groups. Mann-Whitney U test was used to compare continuous variables between the groups. Chi-squared test and Fisher exact test were used to compare categorical variables, as appropriate. A two-tailed p<0.05 was considered significant. Results: There were no differences in changes of cMyC plasma levels, measured at baseline and after the intervention, between patients in the IG and RRE-group (p=0.580). When dividing the entire study population according to Δ VO2Peak higher or lower than median value 0.48 ml/kg/min, we found a statistically significant greater reduction of cMyC values after 12 weeks of exercise training for those with higher than median Delta VO2Peak values compared to those with lower values (p=0.012). This finding was even stronger for the percentage change in cMyC levels (p=0.004 between groups). Conclusion: In patients with symptomatic chronic HFrEF performing a structured 12-week exercise training program, a greater increase in Δ VO2Peak is significantly associated with a reduction in cMyC, suggesting cMyC may provide a dynamic measure of cardiorespiratory state. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Central Norwegian Health authority, Norwegian University of Science and Technology